Metodologi Kajian Islam; Perspektif Ibrahim M. Abu Rabi’ - Anggun Imanto; Mohamad Fatkhul Choiri; Suswanto Suswanto; Muhid Muhid; Kasuwi Saiban (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2023)
Islamic studies (dirosah islamiyyah) should be carried out and developed dynamically like scientific studies in general. But unfortunately on the contrary, Islamic studies seem to have stagnated or not experienced significant progress amidst various social issues that continue to develop. Even when there are Islamic studies conducted by Muslim insiders, they often appear dull and poor in approach and methodology. Islamic studies should be open to the methods and approaches currently being developed. Ibrahim M. Abu Rabi tries to open up this void through his study of the history of Islamic thought and awakens intellectuals so that they fully understand the role and importance of advancing Islamic studies. The scientific opinion is currently being developed. Problems that are increasingly complicated and complex cannot be explained satisfactorily by classical Islamic research theories that rely solely on textual research. According to him, Islamic studies must be open to contemporary scientific disciplines.